Organizing polarized delivery of exosomes at synapses - Mittelbrunn, Maria (Traffic, 2015)
Exosomes are extracellular vesicles that transport different molecules between cells. They are formed and stored inside multivesicular bodies (MVB) until they are released to the extracellular environment. MVB fuse along the plasma membrane, driving non-polarized secretion of exosomes. However, polarized signalling can potentially direct MVBs to a specific point in the plasma membrane to mediate a focal delivery of exosomes. MVB polarization occurs across a broad set of cellular situations, e.g. in immune and neuronal synapses, cell migration and in epithelial sheets. In this review, we summarize the current understanding regarding polarized MVB docking and the specification of secretory sites at the plasma membrane. The current view is that MVB positioning and subsequent exosome delivery requires a polarizing, cytoskeletal dependent- trafficking mechanism. In this context, we propose scenarios in which biochemical and mechanical signals could drive the polarized delivery of exosomes in highly polarized cells, such as lymphocytes, neurons and epithelia.